El asilo político y las tensiones diplomáticas: un análisis jurídico del caso Assange - Delgado Galvis, María Emilia (2024)
The research examines political asylum and diplomacy in depth, focusing on the case of Assange in Ecuador to better understand the rights of asylum seekers. Emphasis is placed on the principle of non-refoulement and non-discrimination in the tensions that arise between nations when granting asylum to individuals persecuted for political reasons. The importance of complying with both international and national laws is highlighted to ensure the protection of those at risk, with special emphasis on equal protection, non-discrimination and the prohibition of return. The methodology used includes legal-doctrinal approaches, case studies, historical-logical and descriptive analyses, with an emphasis on qualitative and bibliographic research, following university guidelines. The detailed analysis of the arguments for and against Assange, as well as the comparison of asylum conventions, provides a comprehensive overview of the case and highlights the relevance of international treaties in this area. The need for an interdisciplinary approach and international cooperation to effectively address diplomatic tensions in political asylum cases is highlighted, highlighting the critical and legal importance of such an approach.